2015
DOI: 10.3389/fnhum.2015.00335
|View full text |Cite
|
Sign up to set email alerts
|

Using brain potentials to understand prism adaptation: the error-related negativity and the P300

Abstract: Prism adaptation (PA) is both a perceptual-motor learning task as well as a promising rehabilitation tool for visuo-spatial neglect (VSN)—a spatial attention disorder often experienced after stroke resulting in slowed and/or inaccurate motor responses to contralesional targets. During PA, individuals are exposed to prism-induced shifts of the visual-field while performing a visuo-guided reaching task. After adaptation, with goggles removed, visuomotor responding is shifted to the opposite direction of that ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 101 publications
8
35
1
Order By: Relevance
“…Although 618 the FRN is classically associated with reinforcement learning, recent work has identified the FRN 619 or the closely related error-related negativity (ERN) in various motor learning and execution tasks 620 involving sensory error signals. These studies either concluded that reinforcement and sensory er-621 ror based learning processes share common neural resources, or they simply do not distinguish 622 between these two processes (Krigolson et al 2008;Torrecillos et al 2014;MacLean et al 2015). 623 We argue that the brain processes reward and sensory error feedback through distinct mechanisms, 624 but that the two processes can be confounded when perturbations causing sensory error are also 625 evaluated as an implicit failure to meet task goals.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Although 618 the FRN is classically associated with reinforcement learning, recent work has identified the FRN 619 or the closely related error-related negativity (ERN) in various motor learning and execution tasks 620 involving sensory error signals. These studies either concluded that reinforcement and sensory er-621 ror based learning processes share common neural resources, or they simply do not distinguish 622 between these two processes (Krigolson et al 2008;Torrecillos et al 2014;MacLean et al 2015). 623 We argue that the brain processes reward and sensory error feedback through distinct mechanisms, 624 but that the two processes can be confounded when perturbations causing sensory error are also 625 evaluated as an implicit failure to meet task goals.…”
mentioning
confidence: 91%
“…25 29 Nikooyan and Ahmed 2015). Electroencephalography (EEG) has been used to identify neural sig-30 natures of error processing in various motor learning and movement execution tasks, but it remains 31 unclear how these neural responses relate to distinct reward and sensory-error based motor learning 32 mechanisms (Krigolson et al 2008;Torrecillos et al 2014;MacLean et al 2015). Here we identified 33 neural signatures of sensory error and reward feedback processing in motor learning using separate 34 learning paradigms that produce comparable changes in behavior.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly some of these signals are of a predictive nature, e.g. they predict upcoming rewards in the case of dopamine or movement errors in the case of the error-related negativity (ERN), see MacLean et al (2015). Furthermore both dopamine signals (Engelhard et al, 2019;Roeper, 2013) and ERN-related neural firing (Sajad et al, 2019) are reported to be specific for a target population of neurons, rather than global.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for simplicity's sake we have chosen to use the error-related negativity label from our original work. See MacLean et al (2015) and our original work, Krigolson and Holroyd (2006), for more detail. 450 [20.20, 20.64], p 5 .001 (see Figure 3).…”
Section: Res Ul Tsmentioning
confidence: 99%